113/5000 The teaching process English language learning: through the digital information and communication technologies / O processo de ensino aprendizagem de língua inglesa: através das tecnologias digitais de informação e comunicação - Gêrlan Cardoso da Silva (Universidade Estadual de Alagoas, 2016)
The school has undergone several transformations and is indispensable currently deny the use of Information and Communication Technology, or ICT, social setting and thus the daily lives of our students, education. Then this article is aiming to present some proposals for activities with the use of technology in English classes in order to reflect on the importance the use of ICT in the current context for teaching and learning a foreign language Modern process. Technology is one of the most efficient tools currently as it relates to information and communication in education, but for lack of information, knowledge, and even teacher training in relation to new technology ends up being rejected and criticized by many. Yet when has the knowledge teachers participate in various pedagogical approaches in their classes with is tool. Since activities Grammar-Translation (direct method) to the Communicative Partner (communicative approach) to have a better result in the teaching-learning process. Some authors as: BRAZIL (1998); MORAES (1996); MARQUES (2003); VYGOTSKY (2001) and other theorists substantiate the assumptions and methodology of this research.